Mixed convection in an inclined lid-driven square cavity with sinusoidal heating on top lid - A. Bakar, N.; Roslan, R.; Ali, M.; Karimipour, A. (Asian Research Publishing Network (ARPN), 2017)
Numerical study on the effect of inclination angle with sinusoidal heating on top moving lid in two-dimensional square cavity is investigated. The top lid is heated sinusoidally while the bottom wall is maintained at cold temperature. The vertical walls are insulated and the cavity is filled with water. Finite volume method and SIMPLE algorithm are employed to solve the dimensionless governing equations. The effect of Richardson number, ranging from 0.1 to 10.0 and inclination angle ranging from 0° to 60° on heat and fluid flow are investigated by utilizing the discretized equations in FORTRAN programming language. The Reynolds number and Prandtl number are fixed. Finally the solutions are discussed using a graphical approach. The results demonstrate that for the case of forced convection and mixed convection dominated regime, heat transfer rate increases with the increase of cavity inclination.